Effect of formulations and adjuvants on the properties of acetamiprid solution and droplet deposition characteristics sprayed by UAV - Zeeshan, Muhammad; Li, Haoran; Yousaf, Gulfam; Ren, Hao; Liu, Yapeng; Arshad, Muhammad; Dou, Zechen; Han, Xiaoqiang (Frontiers in Plant Science, 2024)
While the pesticide formulations are widely used for pest control, the combined effects of these formulations with adjuvants on droplet behavior, spraying characteristics and pest control still need to be studied. To clarify their impact on droplet behavior, spraying characteristics and control efficacy, six formulations of acetamiprid and six adjuvants were examined. A series of laboratory and field experiments were conducted to analyze the physicochemical properties, toxicity against cotton aphids, droplet deposition characteristics, and droplet drift. The results indicated that 5% acetamiprid micro-emulsion (ME) enhanced the physicochemical features and effectiveness in pest control compared to other formulations. The nongjianfei considerably enhanced the efficiency of all acetamiprid formulations when added. The addition of selected adjuvants to pesticide formulations improved the performance of certain physicochemical properties such as viscosity and surface tension and led to higher aphid mortality rates, demonstrating enhanced pest control effectiveness during the present study. In the field experiments, the combination effect of acetamiprid formulations and adjuvants exhibited a higher droplet size, coverage, and density within the cotton canopy. However, 5% acetamiprid ME was found to be most effective followed by nongjianfei. Furthermore, 5% acetamiprid ME with adjuvant reduced the droplet drift and provided better deposition when compared with other formulations. Overall, the combination of specific formulations and adjuvants led to improved physicochemical properties, enhanced droplet deposition characteristics, reduced spray drift and increased pesticide deposition. These findings highlighted the significance of selecting appropriate pesticide formulations and adjuvants and provided a solid foundation for efficient pesticide spraying through UAVs.